Many-photon excitation of organic molecules in a cavity: superradiance as a measure of coherence - Ulusoy, Inga; Gomez, Johana A.; Vendrell, Oriol (The journal of chemical physics, 2020)
Coherent excitation of a molecular ensemble coupled to a common radiation mode can lead to the collective emission of radiation known as superradiance. This collective emission only occurs if there is an entanglement between the molecules in their ground and excited state and can, therefore, serve as a macroscopic measure of coherence in the ensemble. Reported here are wave packet propagations for various pyrazine models of increasing complexity and molecular ensembles thereof. We show that ensemble coherence upon photoexcitation can prevail up to relatively long time scales although the effect can diminish quickly with increasing ensemble size. Coherence can also build up over time and even reemerge after the molecules have passed through a conical intersection. The effect of the pump pulse characteristics on the collective response of the molecular ensemble is also studied. A broadband pulse imprints a large amount of initial coherence to the system, as compared to a longer pulse with a smaller spread in the frequency domain. However, the differential effects arising from a different pulse duration and coherent bandwidth become less prominent if the emission of light from the ensemble takes place after a non-adiabatic decay process.
Gesehen am 28.01.2021